2019
DOI: 10.1016/j.ejca.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A validated prognostic classifier for BRAF-mutated metastatic colorectal cancer: the ‘BRAF BeCool’ study

Abstract: Background: Despite the well-known negative prognostic value of the V600E BRAF mutation in patients with metastatic colorectal cancer (mCRC), its outcome is quite heterogeneous, and the basis for this prognostic heterogeneity should be better defined. Methods: Two large retrospective series of V600E BRAF-mutated mCRC from 22 institutions served as an exploratory and validation set to develop a prognostic score. The model was internally and externally validated. Results: A total of 395 V600E BRAF-mutated mCRCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 30 publications
5
39
1
1
Order By: Relevance
“…However, in the clinic, it has been observed that some patients with BRAFmut tumors have a relatively long survival, despite the mutational status. This was recently explored in study of 395 BRAFmut mCRCs, where clinical prognostic markers defined three vastly different prognostic groups (30). Our study may, at least in part, explain this as it demonstrates that CDX2 expression defines a new prognostic subgroup in patients with BRAFmut (53%) with a much better prognosis, comparable to wild-type patients.…”
Section: Discussionmentioning
confidence: 66%
“…However, in the clinic, it has been observed that some patients with BRAFmut tumors have a relatively long survival, despite the mutational status. This was recently explored in study of 395 BRAFmut mCRCs, where clinical prognostic markers defined three vastly different prognostic groups (30). Our study may, at least in part, explain this as it demonstrates that CDX2 expression defines a new prognostic subgroup in patients with BRAFmut (53%) with a much better prognosis, comparable to wild-type patients.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, Loupakis et al suggested a more practical classification method by using data which were easily available in daily practice, such as performance status (PS) and laboratory data only. Interestingly, they revealed that the prognosis of BRAF-mutated CRCs was clearly divided according to their clinical subtyping [203]. These results indicated that BRAF-mutated CRCs were not one disease but that there was inter-tumor heterogeneity among BRAF-mutated CRCs.…”
Section: Future Perspectives On Braf-mutated Mcrc and Beyondmentioning
confidence: 99%
“…Therefore, since the remarkable prognostic difference between MSS/BRAFmt and MSI/BRAFmt CRCs, even in metastatic settings, molecular subtyping according BRAF mutational status alone is an insufficient prognostic index and the assessment of MMR status should always be performed [15]. In addition, the inclusion of other clinical and laboratory criteria could be useful to better prognostically stratify BRAF mutant patients as recently demonstrated by Loupakis et al [99,100]; items included in this prognostic score are: performance status, CA19.9, LDH, neutrophils/lymphocytes ratio, grading, liver/lung/nodal involvement. Combining these variables authors built both a "complete" prognostic score, and a "simplified" one (excluding laboratory features).…”
Section: Prognostic Impact Of Braf Mutations In Crcmentioning
confidence: 99%